2016
DOI: 10.1148/radiol.2016152510
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma: Intra-arterial Delivery of Doxorubicin-loaded Hollow Gold Nanospheres for Photothermal Ablation—Chemoembolization Therapy in Rats

Abstract: Purpose To determine if combretastatin A-4 phosphate disodium (CA4P) can enhance the tumor uptake of doxorubicin (Dox)-loaded, polyethylene glycol (PEG)-coated hollow gold nanospheres (HAuNS) mixed with Lipiodol (Dox@PEG-HAuNS/Lipiodol) for improved photothermal ablation (PTA)-chemoembolization therapy (CET; PTA-CET) of hepatocellular carcinoma (HCC) in rats. Materials and Methods All animal experiments were approved by the Institutional Animal Care and Use Committee, and were performed in 45 Sprague-Dawley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
0
27
0
1
Order By: Relevance
“…Nevertheless, there was a lack of feedback to allow precise delivery of these therapeutic agents to the target site. In the past years, emerging evidence has showed that several nano/micrometer‐sized materials served as drug‐delivery agents and had less potential damage to surrounding tissues (Li et al, ; Wen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there was a lack of feedback to allow precise delivery of these therapeutic agents to the target site. In the past years, emerging evidence has showed that several nano/micrometer‐sized materials served as drug‐delivery agents and had less potential damage to surrounding tissues (Li et al, ; Wen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Photothermal nanomaterials refer to those that are able to produce a localized heat through plasmonic activation. [16,29,30,[69][70][71] These comprise of nanogold (Au) and nanosilver (Ag) that exist in various shapes such as spherical gold NP (AuNP), [68,70,72,73] gold nanorod (AuNR), [70] hollow gold nanosphere (HAuNS), [41,[74][75][76][77] and porous gold nanocage (AuNC). [69,78,79] Their photothermal activation occurs by irradiation at a visible (vis) and near infrared (NIR) region (500-800 nm).…”
Section: Photothermal Nanomaterialsmentioning
confidence: 99%
“…The produced heat rapidly dissipates, causing a localized hyperthermia which is potent enough to kill cells in a close proximity. [80,81] Besides these functional properties, certain types of nanogold such as HAuNS [41,74,75,77] and AuNC [78,79,82] offer unique structural benefits for drug delivery based on tunable cavities for drug loading and large surface areas available for ligand conjugation. This is illustrated with tumor targeted applications using HAuNS conjugated with folic acid, [83,84] RGD peptide, [41] tumor-specific aptamer, [76] or anti-EGFR antibody, [74] and AuNC conjugated with anti-HER2 antibody.…”
Section: Photothermal Nanomaterialsmentioning
confidence: 99%
“…30,31 However, PTT is restricted by several limitations, including a limited light penetration depth for deeply buried tumors, the possibility of damaging normal tissues, compromised therapeutic effects by threshold laser power for skin tolerance, 32 and low concentrations of nanomaterials in tumors by intravenous administration. 33 Given these issues, the transcatheter intra-arterial infusion has been applied in previous studies, [34][35][36] but studies have seldom evaluated the efficacy of transcatheter intra-arterial infusion combined with IPTT compared with other therapy modalities for hepatic carcinoma. Herein, to improve the therapeutic effect of HCC, we developed a new therapeutic method of transcatheter intra-arterial infusion of Bi-based nanoparticles (Bi-Ln NPs) combined with IPTT.…”
Section: Introductionmentioning
confidence: 99%